Metamorfosis Kebudayaan (Sebuah Tinjauan Media Televisi dan Budaya Kekerasan) - Harsanto, Prayanto Widyo (Institute of Research and Community Outreach - Petra Christian University, 2009)
Culture and communication media cannot be separated one from another, because culture does not only determine who is talking, but also determine about what and how the communication takes place. Culture, in this case, takes a role in determining how the messages are received and meanings are conveyed. The plenty of (visual) mass communication media have succeeded in affirming that globalism has occured everywhere including in Indonesia as a developing country. Television is one sort of mass communication media produced by a long process of human culture development. The intended development is improvement in technological field, specifically in communication and information technology that revolutionize communication techniques. The television mass media have the most powerful effect towards society concerning imitation. Various television programs, especially those that contain violence factors, the violence that is watched by children may stimulate them doing crime in their adulthood. This is because there is a strong relationship between violence on television with factual life. This is a characteristic of media culture that is a kind of visualization culture which can be imitated and followed by anyone. Abstract in Bahasa Indonesia: Budaya dan media komunikasi tidak dapat dipisahkan satu dengan yang lainnya, sebab kebudayaan tidak hanya menentukan siapa yang berbicara, tetapi tentang apa dan bagaimana komunikasi itu berlangsung. Kebudayaan dalam hal ini ikut menentukan bagaimana pesan-pesan ditangkap dan makna-makna disampaikan. Gencarnya media komunikasi massa (visual) telah berhasil mengukuhkan bahwa globalisme telah terjadi di mana-mana termasuk Indonesia sebagai negara berkembang. Televisi merupakan salah satu jenis media komunikasi massa hasil dari suatu proses perkembangan budaya manusia yang panjang. Perkembangan yang dimaksud adalah kemajuan dalam bidang teknologi, khususnya teknologi komunikasi dan informasi yang merevolusi teknik-teknik berkomunikasi. Media massa televisi ini memiliki efek paling kuat terhadap masyarakat dalam hal peniruan. Berbagai program tayangan di televisi khususnya yang mengandung unsur kekerasan, hasil tontonan kekerasan yang dinikmati anak dapat mendorong aksi kriminalitas saat dewasa nantinya. Karena ada hubungan erat kekerasan di tayangan televisi dengan yang terjadi di kehidupan nyata. Ini merupakan ciri khas budaya media adalah bahwa ia merupakan suatu budaya peragaan yang dapat ditiru dan diikuti siapa saja. Kata kunci: kebudayaan, televisi, kekerasan.